The use of illustrative videos in the process of assimilation and fixation of contents, in Science classes in the initial series-O uso de vídeos ilustrativos no processo de assimilação e fixação dos conteúdos, nas aulas de Ciências nas séries iniciais - José Arthur da Silva Santos; Wagner Soares de Lima; Monique Gabriella Angelo da Silva (Universidade Estadual de Alagoas, 2020)
The use of technologies has become indispensable for the process of expanding new methodological practices inside or outside the classroom. They have contributed in a decisive way to the process of socialization and learning in the school space. And, despite the great difficulties often imposed by schools and teachers in inserting the use of these resources in the classroom, they need to be aware of the benefits they bring to the classroom, among them: it allows a greater diversity in activities , thus influencing the exchange of knowledge through hypotheses and questions, thus allowing the construction of new knowledge, the fixation and assimilation of the contents with the help of these tools. The present work brings as a suggestion the incorporation of illustrative videos in science classes as a complementary resource with the objective of verifying in practice what the effective contributions of the use of these resources through the process of assimilation and fixation of the contents in a group of the 3rd year of initial series of Escola de Ensino Fundamental Odilon Pereira Lima, located in the municipality of Cacimbinhas/AL